Utilizing Connection Usage Characteristics for Faster Web Data Transport - Gautam Raj Moktan; Nutti Varis; Jukka Manner (Journal of Computer Networks and Communications)
The quest for faster data transport to improve web user experience is ongoing and attempts are conducted from various fronts to realize it. On top of improving user experience, the implications of improving web data transport are also on the energy efficiency of wireless devices as well as user retention rates of service providers. HTTP/1.x allow the opening of multiple TCP connections per server and then using those connections for fetching multiple web objects through the use of HTTP pipelining. With the advent of HTTP/2.0, multiplexing is done inside a single connection to fetch multiple objects. In this paper, we analyze the TCP connections between the browser and the servers and examine their characteristics. We describe how an enhanced TCP variant can take advantage of data transport connection patterns. We show the benefits that enhanced TCP system can bring with the understanding of connection usage patterns. We find that such transport protocol can have effect in the page idle times as well as the connection concurrency during web page transfer. The results show significant improvement of page load times for both encryption heavy and unencrypted pages. We discuss the effect of the transport protocol on object transfer, connection duration, idle times during the page load, connections, and concurrency of flows that cumulate into page load times.